(untitled) (Research, Society and Development, 2022)
The research objective was evaluate the effect of cooking workshops on the acceptability of products made with spinach residue among children. Also, analyze the physical-chemical composition of the products. Fifty-five school-age children participated in the pre and post-intervention stages. Products tested in the research included patty, pancake and cheese puff, which were added with spinach residue. In the pre-intervention, the products were sensorially analyzed by the children, without carrying out the cooking workshops. In the post-intervention stage, the participants evaluated the products again after participating in the cooking workshops. The physical-chemical composition of the products was analyzed to ensure food and nutritional safety. The cooking workshops raised the grades and the acceptability index of the products (> 70%). The patty had the highest ash, protein, lipid and energy content, while the pancake had the lowest ash, lipid, carbohydrate and energy content. Lower protein and higher carbohydrate contents were found in the cheese puff. Contents of less than 3% of fibers were observed in the products. It is concluded that the cooking workshop improves the acceptability of products added with spinach residue by children, which have a good nutritional profile.